Theological Education at Finkenwalde: 1935-1937 - Bonhoeffer, Dietrich, 1906-1945 (Book collections on Project MUSE., 2014)
In the spring of 1935 Dietrich Bonhoeffer returned from England to direct a small illegal seminary for the Confessing Church. The seminary existed for two years before the Gestapo ordered it closed in August 1937. The two years of Finkenwalde's existence produced some of Bonhoeffer's most significant theological work as he prepared these young seminarians for the turbulence and risk of parish ministry in the Confessing Church. Bonhoeffer and his seminarians were under Gestapo surveillance; some of them were arrested and imprisoned. Throughout, he remained dedicated to training them for the ministry and its challenges in a difficult time. This volume includes bible studies, sermons, and lectures on homiletics, pastoral care, and catechesis, giving a moving and up-close portrait of the Confessing Church in these crucial yearsthe same period during which Bonhoeffer wrote his classics, Discipleship and Life Together.